Abscission-related genes revealed by RNA-Seq analysis using self-abscising apple (Malus × domestica). Issue 3 (3rd May 2016) - Heo, S.; Hwang, J. H.; Jun, J. H.; Lee, H. J.
ABSTRACT: The self-abscising characteristic of apple ( Malus × domestica ) fruit is a prominent labour-saving trait during cultivation. Early abscission up to 30 d after full bloom leaves only the central fruit in a cluster, while the four lateral fruit are abscised. A comparative analysis was conducted between the central and lateral pedicels in the self-abscising apple cultivar 'Saika' to identify the genes that trigger the abscission mechanism, as the destinies of the pedicels in a cluster are obvious. Transcriptome analysis was performed using RNA-Seq to compare expression profiles between the surviving central pedicel and the abscised lateral pedicels. A total of 797, 647 expressed sequence tags were assembled into 65, 876 contigs, which were annotated and analysed using Blast2GO. A total of 1, 585 differentially expressed genes were identified in the central and lateral pedicels using NOISeq software. Differentially expressed genes were confirmed by quantitative real-time reverse-transcription polymerase chain reaction analysis, focussing on the genes associated with auxin signalling. Our data suggested that the IAA14 / SLR gene is at least partly involved in the mechanism of abscission of the lateral pedicels.